Linking knowledge and industry needs through problem-based learning in power electronics course - Hussain I.S.; Jaafar S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Curricula; Education; Electronics industry; Engineering education; Power electronics; Students; Torque converters; Group work; Industrial practices; Industry needs; Learning Activity; Malaysia; Power electronics course; Problem based learning; Student-based; E-learning